2021
DOI: 10.1016/s2213-2600(20)30519-1
|View full text |Cite
|
Sign up to set email alerts
|

Juntos en la pandemia de COVID-19 (together in the COVID-19 pandemic): health-care professionals and the Latinx community

Abstract: experiential learning liable to bring a great many people to discover the overlooked existential experience of dyspnoeic patients. We believe that this offers a unique opportunity to raise public awareness of what it means to be constantly aware of, and bothered by, one's own breathing. This phenomenon could be leveraged by foundations and charities that promote lung health or by teams engaged in the field of disability studies as a communication tool about the dyspnoeic experience that is lived by patients af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In health-related matters, cultural competency -having knowledge of a group's cultural perspectives and typical behaviors or beliefs -is necessary to bridge cultural boundaries (20). For example, communication with racial and ethnic minority communities should be in their preferred language (21), culturally relevant, and contain culturally appropriate colors, images, and pictures (22).…”
Section: Discussionmentioning
confidence: 99%
“…In health-related matters, cultural competency -having knowledge of a group's cultural perspectives and typical behaviors or beliefs -is necessary to bridge cultural boundaries (20). For example, communication with racial and ethnic minority communities should be in their preferred language (21), culturally relevant, and contain culturally appropriate colors, images, and pictures (22).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study showed that the Latin population had a higher risk of hospitalization ( Zaeh et al, 2021 Jan ). In our study, patients from America took longest to visit the emergency department and consulted their primary care doctor the least.…”
Section: Discussionmentioning
confidence: 99%
“…37 They also created a service of bilingual healthcare providers to help provide effective communication to Spanish-only speaking patients in the emergency department and inpatient COVID-19 units. 38 Training the healthcare workforce, adapting to changes with an eye on efficiency, striving for premium quality, emphasising the importance of effective communication, focusing on physician wellbeing and addressing systemic inequities in access to care are vital to 'normal' clinical practice within our complex medical systems. The value of these elements is only multiplied in the face of a crisis, reminding us that many of our everyday clinical skills translate well to crisis management.…”
Section: Reviewmentioning
confidence: 99%
“…For example, clinicians from our institution hosted weekly Facebook Live events in Spanish, spoke with community advocates to provide up to date information on COVID-19, and even regularly met with Latinx individuals waiting to be hired as day labourers outside Home Depot 37. They also created a service of bilingual healthcare providers to help provide effective communication to Spanish-only speaking patients in the emergency department and inpatient COVID-19 units 38…”
Section: Application Of the Definition Of Clinical Excellence To The ...mentioning
confidence: 99%